Pengaruh Big Data Terhadap Value Perusahaan Dengan Keputusan Investasi Sebagai Variabel Intervening - Zulyanda, Yogi; Yuhefizar, Yuhefizar; Fontanella, Amy (Akuntansi dan Manajemen, 2024)
In the current era of digitalization, big data has become one of the most valuable assets for companies to increase efficiency and competitiveness. This research aims to determine the influence of Big Data on Company Nilai with Investment Decisions as an Intervening Variable. The type of quantitative research and population are Technology Sector Companies Listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. Sampling used a purposive sampling method to obtain 7 companies with a research period of 5 years using quarterly data.The analysis method used is panel data regression to test the direct relationship between variables and SEM to test the mediation relationship. Data processing uses the STATA application. The results of this research show that (a) big data partially has no significant effect on company nilai (b) big data partially has a significant effect on investment decisions (c) partial investment decisions have no significant effect on company nilai (e) big data partially has no significant effect on company nilai with investment decisions as an intervening variable. These findings show that although big data influences investment decisions, its impact on company value is not yet optimal.